The young Messiah [videorecording (DVD)] - Nowrasteh, Cyrus; Greaves-Neal, Adam; Lazzaro, Sara; Walsh, Vincent, 1972-; Bean, Sean; Rice, Anne, 1941- (Universal Pictures Home Entertainment, 2016)
The inspiring and unique story of seven-year-old Jesus Christ and His family as they come to a fuller understanding of His divine nature and purpose.